Moderniosios Lietuvos želmenų XIX amžiuje beieškant: Aleksandro Burbos „Senybinis aukuras“ – 1881 metų patriotinės eilės broliams lietuviams - Vyšniauskas, Arūnas (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]Published in the article as both a work of poetry and a historical source is the poem Senybinis aukuras (“An Olden Altar”), written in Lithuanian in 1881 by the then-26-years-old Aleksandras Burba, a cleric of the Vilnius priest seminary. The essence of its Lithuanian patriotism, grounded on the notion of the emancipation of a Lithuanian-speaking territory, is revealed. It is argued that this poem, first published in 1885, is important for historical recognition as a primary historical source. Attention is also paid to a revised version of the poem, published in 1893, which was slightly edited in accordance with the changed realities of that time. In terms of genre, the poetic work of A. Burba Senybinis aukuras may be considered a literary ballad, typologically attributed to the type of the national ballad. In this patriotic ballad, we find an alloy of an exalted Lithuanian antiquity, a somber-esque portrayal of that period (c. 1881), an incitement to act and an optimistic future. The original narrative laid out in an elevated and emotional tone, complete with interjections, exclamations, a dialogue reminiscent of the present, a mentioning of topical subjects, a depreciation of the disavowing of the language for the benefit of the Poles etc., should be treated as a peculiar literary monument from which we can judge about the poet’s space of thoughts in terms of various aspects. The act proceeds by narrating a journey in a naturalistic setting in two stages. First through a route between Ignalina and Vidiškės; later, a departure from Vidiškės takes place toward the mysterious olden altar – a sacred place recalling the times of pagan worship. In the ballad, an ever-rising tension is maintained with the finalistic structure, and the verses see an entanglement of epic, dramatic and lyrical components. An appeal is made to the revival of the forebears’ spirit; the Lithuanian spirit is revealed by relying on the ancient past, not unwilling to relate it with Christianity in the present and with godly assistance in the future. The „olden altar“, exalted in the verses of A. Burba, was located on the outskirts of the Dūdos folwark, near the cemetery of the Antakmenė village, and remains there to this day. It is a designated archeological monument and a state-protected geological heritage site. It is offered to promote it further for purposes both tourism-related and otherwise by linking it with the meanings of A. Burba’s poetic creation, which are examined in this article through various aspects. The analysis of this particular as much as other poetic works of the 19th century can be beneficial not only to philologists and literary theorists but to historians as well, as the verses written under the conditions of the hounding of the Lithuanian language and the prohibition of the press become an important source for recognizing the mindsets, worldviews and environments of the past generations. Witness accounts, conveyed alongside feelings and experiences by the poets in their works, often possess a certain worth as documentary / egodocumentary elements, the analysis and disclosure of which is a delicate task for the researchers of the past.
Keywords: Burba, Aleksandras; Gimžauskas, Silvestras; stone; altar; conglomerate; Antakmenė; Dūdos; Vidiškės; Ignalina; Lithuania; Lithuanians; Latvians; Balts; balladpast